2010
DOI: 10.1007/s11999-010-1324-6
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Sponges to Locally Deliver Amikacin and Vancomycin: A Pilot In Vitro Evaluation

Abstract: Background Open orthopaedic wounds are ideal sites for infection. Preventing infection in these wounds is critical for reducing patient morbidity and mortality, controlling antimicrobial resistance and lowering the cost of treatment. Localized drug delivery has the potential to overcome the challenges associated with traditional systemic dosing. A degradable, biocompatible polymer sponge (chitosan) that can be loaded with clinician-selected antibiotics at the point of care would provide the patient and clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 32 publications
5
98
1
1
Order By: Relevance
“…Another study used a porous chitosan sponge for absorption of amikacin and vancomycin antibiotics in solution over 72h. The in vitro elution results showed that chitosan sponge loaded with an antibiotic can be used as drug carrier for treating and protecting wounds against infections (Noel et al, 2010).…”
Section: Film Sponge and Powdermentioning
confidence: 99%
“…Another study used a porous chitosan sponge for absorption of amikacin and vancomycin antibiotics in solution over 72h. The in vitro elution results showed that chitosan sponge loaded with an antibiotic can be used as drug carrier for treating and protecting wounds against infections (Noel et al, 2010).…”
Section: Film Sponge and Powdermentioning
confidence: 99%
“…43 Noel et al 44 and Smith et al 45 suggested the possibility of using a CS sponge device as an alternative to deliver antibiotics locally as an adjunctive therapy for the treatment and prevention of infections, from open traumatic wounds to prophylactic use in surgical sites. Furthermore, a CS sponge can be used as a drug reservoir 43 or a storage form for CS systems.…”
Section: Morphological Characteristics Of Ace-np and Spongesmentioning
confidence: 99%
“…Local drug delivery carriers, such as calcium sulfate, collagen, or chitosan, have been effective in targeted, local delivery of C2DA [22,26,41]. For these initial pilot studies, the chitosan sponge was chosen for evaluation because it was a biocompatible delivery device that released antimicrobial compounds at therapeutic levels [36,41]. To establish the preliminary feasibility of local delivery of C2DA, the effects of inhibitory concentrations of C2DA on cell survival and proliferation should be evaluated to determine potential cytotoxic effects and to optimize dosing strategies.…”
Section: Introductionmentioning
confidence: 99%